1993
DOI: 10.1203/00006450-199302000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Responses to Hyperoxia in Preterm and Term Rats after Prenatal Dexamethasone Administration

Abstract: ABSI'RACI'. Although prenatal steroid therapy is known to enhance in utero maturation of the surfactant and antioxidant enzyme systems, little is known about the effects of steroids on the antioxidant system after birth. We measured activities of the antioxidant enzymes, catalase, superoxide dismutase, and glutathione peroxidase, in lung homogenates from both preterm and term rat pups after prenatal dexamethasone treatment. Enzyme activities were measured at birth and after exposure to >98% oxygen. Dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This finding may be explained by the fact that SOD is considered to be the first line of defense against oxygen toxicity. Antenatal steroid therapy may accelerate antioxidant enzyme activity 29–31 . High SOD activity could not be attributed to the effect of steroid therapy in the present study because of the fact that there was no significant difference in the use of antenatal steroid between groups.…”
Section: Discussionmentioning
confidence: 52%
“…This finding may be explained by the fact that SOD is considered to be the first line of defense against oxygen toxicity. Antenatal steroid therapy may accelerate antioxidant enzyme activity 29–31 . High SOD activity could not be attributed to the effect of steroid therapy in the present study because of the fact that there was no significant difference in the use of antenatal steroid between groups.…”
Section: Discussionmentioning
confidence: 52%
“…As survival remained better in the group treated antenatally, it may be that it is the rate of increase in antioxidant enzymes rather than simple increases in these enzymes which is more important. Prematurely delivered rat pups were studied by Keeny et al, 33 who showed that the survival of the preterm pups in the group treated antenatally was significantly better than in the untreated group at 24 hours of age (91% vs 57%). Increases were seen at 24 hours of age in antioxidant enzymes in the treated group, as in Frank’s study, with no significant differences being seen after this age in both the treated and untreated groups.…”
Section: Effects Of Corticosteroids On the Antioxidant Systemmentioning
confidence: 99%
“…Exposures to oxygen were performed in airtight plastic cages as previously described (20). Oxygen was humidified, provided at a flow rate of 5.0 Llmin, and continuously analyzed.…”
Section: Animals Adult Malementioning
confidence: 99%